Evaluating Glycemic Control in Patients of South Asian Origin With Type 2 Diabetes Using a Digital Therapeutic Platform: Analysis of Real-World Data - Krishnakumar, Arjun; Verma, Ritika; Chawla, Rajeev; Sosale, Aravind; Saboo, Banshi; Joshi, Shilpa; Shaikh, Maaz; Shah, Abhishek; Kolwankar, Siddhesh; Mattoo, Vinod (JMIR Publications, 2021)
BackgroundDigital therapeutics are evidence-based therapeutic interventions driven by high-quality software programs for the treatment, prevention, or management of a medical disorder or disease. Many studies in the western population have shown the effectiveness of mobile app-based digital therapeutics for improving glycemic control in patients with type 2 diabetes (T2D). However, few studies have assessed similar outcomes in the South Asian population. ObjectiveThis study aims to investigate the real-world effectiveness of the Wellthy CARE digital therapeutic for improving glycemic control among the South Asian population of Indian origin. MethodsWe analyzed deidentified data from 102 patients with T2D from India enrolled in a 16-week structured self-management program delivered using the Wellthy CARE mobile app. Patients recorded their meals, weight, physical activity, and blood sugar in the app, and they received lessons on self-care behaviors (healthy eating, being active, monitoring, medication adherence, problem solving, healthy coping, and reducing risks); feedback provided by an artificial intelligence-powered chatbot; and periodic interactions with certified diabetes educators via voice calls and chats. The primary outcome of the program was a change in glycated hemoglobin A1c (HbA1c). Secondary outcomes included the difference between preintervention and postintervention fasting blood glucose (FBG) and postprandial blood glucose (PPBG) levels; changes in BMI and weight at the completion of 16 weeks; and the association between program engagement and the changes in HbA1c, FBG, and PPBG levels. ResultsAt the end of 16 weeks, the average change in HbA1c was -0.49% (n=102; 95% CI −0.73 to 0.25; P<.001). Of all the patients, 63.7% (65/102) had improved HbA1c levels, with a mean change of −1.16% (n=65; 95% CI −1.40 to −0.92; P<.001). The mean preintervention and postintervention FBG levels were 145 mg/dL (n=51; 95% CI 135-155) and 134 mg/dL (n=51; 95% CI 122-146; P=.02) and PPBG levels were 188 mg/dL (n=51; 95% CI 172-203) and 166 mg/dL (n=51; 95% CI 153-180; P=.03), respectively. The mean changes in BMI and weight were -0.47 kg/m2 (n=59; 95% CI −0.22 to −0.71; P<.001) and -1.32 kg (n=59; 95% CI −0.63 to −2.01; P<.001), respectively. There was a stepwise decrease in HbA1c, FBG, and PPBG levels as the program engagement increased. Patients in the highest tertile of program engagement had a significantly higher reduction in HbA1c (−0.84% vs −0.06%; P=.02), FBG (−21.4 mg/dL vs −0.18 mg/dL; P=.02), and PPBG levels (−22.03 mg/dL vs 2.35 mg/dL; P=.002) than those in the lowest tertile. ConclusionsThe use of the Wellthy CARE digital therapeutic for patients with T2D showed a significant reduction in the levels of HbA1c, FBG, and PPBG after 16 weeks. A higher level of participation showed improved glycemic control, suggesting the potential of the Wellthy CARE platform for better management of the disease.